Antihyperglycemic Activity of Eucalyptus tereticornis in Insulin-Resistant Cells and a Nutritional Model of Diabetic Mice - Alis Guillén; Sergio Granados; Kevin Eduardo Rivas; Omar Estrada; Luis Fernando Echeverri; Norman Balcázar (Hindawi Limited, 2015)
Eucalyptus tereticornis is a plant used in traditional medicine to control diabetes, but this effect has not been proved scientifically. Here, we demonstrated through in vitro assays that E. tereticornis extracts increase glucose uptake and inhibit their production in insulin-resistant C2C12 and HepG2 cells, respectively. Furthermore, in a nutritional model using diabetic mice, the administration of ethyl acetate extract of E. tereticornis reduced fasting glycaemia, improved tolerance to glucose, and reduced resistance to insulin. Likewise, this extract had anti-inflammatory effects in adipose tissue when compared to control diabetic mice. Via bioguided assays and sequential purification of the crude extract, a triterpenoid-rich fraction from ethyl acetate extracts was shown to be responsible for the biological activity. Similarly, we identified the main compound responsible for the antihyperglycemic activity in this extract. This study shows that triterpenes found in E. tereticornis extracts act as hypoglycemic/antidiabetic compounds and contribute to the understanding of their use in traditional medicine.